PIAS3 promotes ferroptosis by regulating TXNIP via TGF-β signaling pathway in hepatocellular carcinoma - Wenfang Bao; Jialin Wang; Kailing Fan; Yong Gao; Jingde Chen (Elsevier, 2023)
Ferroptosis has been suggested to play a potential role in cancer therapy as an iron-dependent programmed cell death mechanism distinct from other forms. Hepatocellular carcinoma (HCC) remains a great threat, with high mortality and limited therapeutic options. The induction of ferroptosis has emerged as a novel and promising therapeutic strategy for HCC. In the present study, we identified protein inhibitor of activated STAT3 (PIAS3) as a driver of ferroptosis in HCC using TMT-based quantitative proteomics and ferroptosis-related functional assays. Mechanistically, thioredoxin-interacting protein (TXNIP) was confirmed to be PIAS3 in promoting ferroptotic cell death, based on RNA-seq analysis. Knockdown of TXNIP degrades ferroptotic susceptibility caused by PIAS3-overexpression, whereas transfection-forced reexpression of TXNIP restores sensitivity to ferroptosis in PIAS3-downregulated cells. PIAS3 interacts with SMAD2/3 to activate transforming growth factor (TGF)-β signaling, leading to increased TXNIP expression. Our study revealed the critical role of PIAS3 in ferroptosis and a novel actionable axis-PIAS3/TGF-β/TXNIP that could govern ferroptotic sensitivity, paving the path for using ferroptosis as an efficient approach in HCC therapies.